(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: The aim of this research paper is to follow the process of social learning in the newborn, via two concepts (imitation, modeling). Controversial results indicate that the newborn may imitate adult gestures. Imitative activities of infants between one and six months are not well known. Imitative behavior then becomes more frequent and more refined. This development is achieved through reinforcement and reciprocal play between the adult and the infant, while interactions with peers, or with strangers. Imitation and modeling are models of social learning that are characterized by observation in the first instance. Observation of behavior of the other participates in the socialization of the human person and in his acculturation. However, its functional aspects are poorly known in early childhood. Keywords: Social learning; Imitation; Modeling; Early childhood